2017
DOI: 10.1371/journal.pone.0173626
|View full text |Cite
|
Sign up to set email alerts
|

Hard clam walking: Active horizontal locomotion of adult Mercenaria mercenaria at the sediment surface and behavioral suppression after extensive sampling

Abstract: Locomotion of infaunal bivalve mollusks primarily consists of vertical movements related to burrowing; horizontal movements have only been reported for a few species. Here, we characterize hard clam walking: active horizontal locomotion of adults (up to 118 mm shell length, SL) of the commercially important species, Mercenaria mercenaria, at the sediment surface—a behavior only briefly noted in the literature. We opportunistically observed walking over a 10-yr period, at 9 different sites in the Peconic Bays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Fertilization efficiency is a serious constraint for free-spawning species (Levitan 2006, Luttikhuizen et al 2011. Recently, Tettelbach et al (2017) found evidence for horizontal movement, dubbed "hard clam walking," in Mercenaria mercenaria, in which both hard clam sexes were equally as likely to "walk" toward a member of the opposite sex. This behavior has not been documented in Arctica islandica, but it has in other clams, such as Spisula solidissima (Tettelbach et al 2017).…”
Section: More Reproductive Chances For Malesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilization efficiency is a serious constraint for free-spawning species (Levitan 2006, Luttikhuizen et al 2011. Recently, Tettelbach et al (2017) found evidence for horizontal movement, dubbed "hard clam walking," in Mercenaria mercenaria, in which both hard clam sexes were equally as likely to "walk" toward a member of the opposite sex. This behavior has not been documented in Arctica islandica, but it has in other clams, such as Spisula solidissima (Tettelbach et al 2017).…”
Section: More Reproductive Chances For Malesmentioning
confidence: 99%
“…Recently, Tettelbach et al (2017) found evidence for horizontal movement, dubbed "hard clam walking," in Mercenaria mercenaria, in which both hard clam sexes were equally as likely to "walk" toward a member of the opposite sex. This behavior has not been documented in Arctica islandica, but it has in other clams, such as Spisula solidissima (Tettelbach et al 2017). Observations of A. islandica movement have been limited to burrowing behavior (Taylor 1976, Strahl et al 2011, and the degree to which horizontal movement is common within the order Venerida is unknown.…”
Section: More Reproductive Chances For Malesmentioning
confidence: 99%
“…Crawling locomotion is broadly defined as movement across a surface in which forward progression is enabled by body movements rather than limb movements [1]. A diverse array of animals demonstrate crawling locomotion including insect larvae [10], worms [11], clams [12,13], and snakes [14]. Similarly, many bioinspired crawling robots have been built and studied across a wide array of mechanical designs including soft-bodied, origami, and rigid crawling robots [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many examples are available of fisheries being overfished to the point where recruitment declines and the stock collapses (Cushing 1971, Hilborn & Walters 1992, Myers et al 1996, shellfish are no exception (Jackson et al 2001, Tettelbach et al 2013. For sessile and sedentary species, the potential of Allee effects cannot be discounted (Shepherd et al 1998, Kraeuter et al 2005, Tettelbach et al 2013, although behavioral adaptations may mitigate the probability (Buroker 1983, Ambrogio & Pechenik 2009, Tettelbach et al 2017). An example is the hard clam Mercenaria mercenaria, where unsustainable fishing mortality led to recruitment overfishing in both North Carolina and New York (Peterson 2002, Kraeuter et al 2005.…”
Section: Introductionmentioning
confidence: 99%